Date delivery scheme of delay-tolerant mobile sensor networks for high-voltage power transmission line inspection robot - FAN Fei; WU Gong-ping; WANG Man; XU Qing-shan; CAO Qi; YANG Song (工程科学学报)
To improve the level of intelligent monitoring, maintenance, and management of transmission lines, research on inspection robots, and key technologies of overhead transmission line have attracted wide attention. With the breakthrough of the theory and technology of the internet of things, robot data transmission based on wireless sensor networks has become an active research area in the field of inspection robotics. Several researchers assume that robots are mobile nodes in wireless sensor networks, and the non-mobile communication node in the network is considered as a static node. The most crucial and difficult aspect of this research is coordinating the relationship among transmission success rate, transmission energy consumption, and delay of dynamic sensors networks. To address this difficulty, a novel method was proposed for the intelligent monitoring and communication system of power grids based on inspection robots. This method aims to realize the remote data collection of inspection robot by delay-tolerant mobile sensor networks for inspection robot (DTMSNR), which is featured by nodes heterogeneity, sparse sensor fields, random mobility, intermittent connectivity, and delay tolerance. It adopts the mobile robot position-based delivery (MPD) method to solve the inadaptability of the traditional methods of sensor networks. A path-constrained random motion model was established, in order to accurately calculate the network pose information of the inspection robot. The MPD adopts the relative position information of the robot and other nodes to compute transmission probability and selects the message transmission path. This method uses mechanisms of robot message priority transfer and failure time to manage the message queue, considering the different delay requirements for messages. Multiple simulation scenarios were performed, and the influences of different parameters with four routing algorithms were discussed. The results indicate that compared with the commonly used DTMSN data transmission methods, the proposed method can provide a higher delivery ratio and lower transport delay under appropriate transmission energy consumption.